2003
DOI: 10.1002/bit.10696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silkworm hemolymph on N‐linked glycosylation in two Trichoplusia ni insect cell lines

Abstract: A recombinant N-linked glycoprotein, secreted human placental alkaline phosphatase (SEAP), was produced in two Trichoplusia ni insect cell lines using the baculovirus expression vector. Silkworm hemolymph (SH) was added to TNMFH + 10% fetal bovine serum (FBS) medium to a concentration of 2.5% or 5%, and SEAP production and glycosylation in the presence of SH were compared with controls devoid of hemolymph. Growing Tn-4s cells in 5% SH-supplemented medium required progressive adaptation of the cells to SH, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…A higher initial concentration of cells could be used to achieve the same amount of recombinant protein. It should be noted that our results are consistent with other expression systems, where supplementation has had beneficial results on glycosylation and slightly detrimental effects on cell growth and/or recombinant protein production (Donaldson et al, 1999;Gawlitzek et al, 2000;Joosten et al, 2003). In addition, the detrimental effects of the supplements used on plant cell growth have been documented and our data are consistent such previous findings (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…A higher initial concentration of cells could be used to achieve the same amount of recombinant protein. It should be noted that our results are consistent with other expression systems, where supplementation has had beneficial results on glycosylation and slightly detrimental effects on cell growth and/or recombinant protein production (Donaldson et al, 1999;Gawlitzek et al, 2000;Joosten et al, 2003). In addition, the detrimental effects of the supplements used on plant cell growth have been documented and our data are consistent such previous findings (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, the silkworm hemolymph (SH) of Bombyx mori was shown to exhibit anti‐apoptotic properties in insect and mammalian cells. Also, apoptosis was inhibited by 30K gene and recombinant protein from SH .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation reflects a fundamental difference between the N-glycan processing pathways of lepidopteran insect and mammalian cells, as most evidence indicates that the former lack functional levels of sialyltransferases (Butters et al, 1981;Stollar et al, 1976) and CMP-sialic acids (Hooker et al, 1999;Tomiya et al, 2001). Clearly, there are some published results that raise questions about the overall generality of this conclusion as it applies to lepidopteran (Davidson et al, 1990;Joosten et al, 2003;Shuler, 2003a, 2003b;Joshi et al, 2001;Palomares et al, 2003;Watanabe et al, 2001) and other (Kim et al, 2002;Koles et al, 2004) insect systems. However, the fact remains that most recombinant N-glycoproteins produced by the most commonly used baculovirus-insect cell combinations are not terminally sialylated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is clear that it will be necessary to survey the ability of this transgenic insect cell line to support sialylation of a much larger and broader array of recombinant glycoprotein products before drawing any sweeping conclusions. In context of this discussion, it is interesting to note that many of the studies reporting recombinant glycoprotein sialylation with the baculovirusinsect cell system have used human secreted alkaline phosphatase as the model glycoprotein (Joosten and Shuler, 2003a, b;Joosten et al, 2003Joosten et al, , 2001Palomares et al, 2003). Perhaps this particular product has some biophysical properties that make its N-glycans particularly amenable to elongation or resistant to deglycosylation.…”
Section: Discussionmentioning
confidence: 99%